Perspectives on Technology, Society and Innovation. Report on the 4S/EASST Joint Conference “Design and Displacement”, Copenhagen, Denmark, October 17–20, 2012 - Nuno Boavida; Torsten Fleischer; Sophie Kuppler; Andreas Lösch; António B. Moniz; Jens Schippl; Judith Simon (Technikfolgenabschätzung – Theorie und Praxis, 2012)
To focus on processes of scientific and technological design and on how newly designed objects are used in different ways than initially intended (“displaced”), the organizers (the Society for Social Studies on Science-4S and the European Association of Studies on Science and Technology-EASST) chose the conference theme “Design and Displacement”.
Keywords: O33; O35; E61; 330; Science; Public Engagement; Socio-technical Systems; Governance; Technology; Values; Innovation; Work; Energy transition